2017
DOI: 10.1186/s12870-017-1065-8
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analysis of WOX genes in upland cotton and their expression pattern under different stresses

Abstract: BackgroundWUSCHEL-related homeobox (WOX) family members play significant roles in plant growth and development, such as in embryo patterning, stem-cell maintenance, and lateral organ formation. The recently published cotton genome sequences allow us to perform comprehensive genome-wide analysis and characterization of WOX genes in cotton.ResultsIn this study, we identified 21, 20, and 38 WOX genes in Gossypium arboreum (2n = 26, A2), G. raimondii (2n = 26, D5), and G. hirsutum (2n = 4x = 52, (AD)t), respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
110
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(123 citation statements)
references
References 63 publications
11
110
2
Order By: Relevance
“…After gene duplication, the new gene could be considered a redundant gene compared with the existing gene, and it can be considered a driving force for evolutionary innovation [61]. Inserting or deleting tissue-specific enhancers or repressors in the coding regions of duplicated genes could obtain a new regulatory context, which might be the cause of functional divergence [62]. Overexpression of GhCIPK6 in cotton could reduce oil content, and increased C18:1 and C18:1+C18:1d6 in transgenic cotton lines, as compared to wild-type plants (Figure 7), indicated that GhCIPK6 plays a negative role in oil synthesis.…”
Section: Expression Patterns Of Ghcipk Gene Family and The Role Of Ghmentioning
confidence: 99%
“…After gene duplication, the new gene could be considered a redundant gene compared with the existing gene, and it can be considered a driving force for evolutionary innovation [61]. Inserting or deleting tissue-specific enhancers or repressors in the coding regions of duplicated genes could obtain a new regulatory context, which might be the cause of functional divergence [62]. Overexpression of GhCIPK6 in cotton could reduce oil content, and increased C18:1 and C18:1+C18:1d6 in transgenic cotton lines, as compared to wild-type plants (Figure 7), indicated that GhCIPK6 plays a negative role in oil synthesis.…”
Section: Expression Patterns Of Ghcipk Gene Family and The Role Of Ghmentioning
confidence: 99%
“…Each AtSWEET gene corresponded to approximately one to ten cotton SWEET genes, respectively. The naming rules were performed based on a published paper (Yang et al 2017). Ga, Gr, Gh, Gb, and At were used as prefixes before the names of SWEET genes from G. arboreum, G. raimondii, G. hirsutum, G. barbadense, and Arabidopsis, respectively.…”
Section: Gene Identification and Conserved Domain Retrievalmentioning
confidence: 99%
“…A line between two genes indicates a paralog genes during growth and development of G. hirsutum plant. The transcription levels in various tissues or organs of RNA-seq data from NCBI and COTTONFGD (http:// www.cottonfgd.org/) were downloaded and analyzed (Yuan et al 2015;Yang et al 2017), including the vegetative (root, stem, and leaf) and reproductive (torus, petal, stamen, pistil, calycle, − 3 and − 1 days post anthesis (DPA) ovule, 0, 1, 3, 5, 10, 20, 25, and 35 days post anthesis (DPA) seed) tissues as well as in the fiber (5, 10, 20, and 25 DPA), and germinating seeds at 0 h, 5 h,10 h and from roots and cotyledons at 24 h, 48 h, 72 h, 96 h, and 120 h after imbibition. Their expression levels were varied (Figs.…”
Section: Expression Patterns Of Sweet Genes In Different Tissuesmentioning
confidence: 99%
“…Each sample was sequenced at~309 coverage of the assembled genome with 150-bp paired-end reads for each sample from the Illumina HiSeq X-ten platform. For mRNA-seq, total RNA was extracted with a previously reported workflow (Qin et al, 2018;Yang et al, 2017;Yang et al, 2018;Zhang et al, 2019). The mRNA was used to synthesis cDNA for building paired-end sequencing libraries.…”
Section: Sampling and Sequencingmentioning
confidence: 99%
“…The petal, flowering bud, stamen, fibre (10 DPA), root, stem cotyledon, hypocotyl, leaf and foliar nectary were harvested for qPCR analysis. The total RNA was extracted using a previous workflow (Qin et al, 2018;Yang et al, 2017;Yang et al, 2018;Zhang et al, 2019). The cDNA was synthesized using PrimeScript RT reagent Kit with gDNA Eraser (Takara, China).…”
Section: Rna-seq and Qpcr Analysismentioning
confidence: 99%